Rural Women’s Political Participation in China: An Analysis of The Methods of Rural Governance Modernization - Zhou Xuqing; Lai, Yew Meng (Penerbit UMS, 2023)
With the development of China’s industrialization and urbanization, many young and middle-aged men in rural China have moved to urban areas to work. The elderly, women and children are the main permanent residents in rural China, and women account for more than half of the agricultural labour force. However, Chinese rural women are obviously in a weak and marginal position in rural political participation, which is not equal to their contribution to rural development. In 2019, China announced plans to modernize rural governance. The core is to adapt to the change of time, reform the rural governance system that does not meet the requirements of practice and development, improve the new rural governance system that combines autonomy, rule of law, and rule of virtue under the leadership of party organizations, make the rural systems more scientific and perfect, and realize the institutional, standardized, and procedural governance of rural social affairs. Rural governance is the basis of national governance. Without the modernization of rural governance, there will be no modernization of national governance, and there will be no modernization of the country. At present, China is in the stage of building socialist modernization in an all-round way, and the modernization of rural governance has been put on the agenda. Therefore, this paper assumes that the modernization of rural governance in China provides a good opportunity to improve the political participation of Chinese rural women. It aims to explore effective approaches to enhancing the level of political participation among rural women and promoting the process of rural democratization in China within the context of rural governance modernization. It achieves this by examining the primary issues surrounding the current political participation of rural women in China and analyzing the main factors contributing to these issues.